Degassing of volatiles in the geological history of Mars - Héctor Javier Durand-Manterola (Geofísica Internacional, 2003)
I obtain an estimate of the total mass of degassed volatiles on Mars and the distribution of degassing in time. The amount of volatiles degassed in all the history of Mars is of the order of 3.73x1020 kg, i.e. 16 000 times the current Martian atmosphere. The bulk of the degassing occurred in Early, Middle, and Late Noachian, and in Early Hesperian. Degassing was monotonically decreasing in the last five epochs, from Early Hesperian to Late Amazonian. The amount of liquid water at the surface in the past was very little or none, thus the existence of life is doubtful.